A survey on the frequency of polycystic ovary morphology (PCOM) in infertile patients with septate and arcuate uterine anomalies: a cross-sectional study - Shohreh Irani; Atiyeh Najafi; Samira Vesali; Mehri Mashayekhi; Fatemeh Niknejad; Firoozeh Ahmadi (Scientific Reports)
Abstract Polycystic ovarian syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age. Previous research has highlighted a potential link between PCOS and Müllerian anomalies. The present cross-sectional study aimed to evaluate the prevalence of polycystic ovary morphology (PCOM) in infertile patients with uterine anomalies (septate and arcuate uterine), attending the Royan Research Institute in Tehran, Iran, between January 2021 and December 2022. A total of 884 infertile women who underwent 3D-hysterosonography at the Institute were included in the study. The participants were divided into two groups: 127 women with uterine anomalies and 757 women without. Data was collected from the participants’ medical records. The results showed that the frequency of PCOM was significantly higher in women with uterine anomalies (40.9%, 52 women) compared to those without such anomalies (14.7%, 111 women) (p = 0.0001). A higher prevalence of PCOM in women with uterine anomalies highlights the need for targeted screening within this population and underscores the importance of integrated diagnostic approaches.